2018
DOI: 10.2139/ssrn.3198112
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Productively Reincorporate the Formerly-Incarcerated into Communities: A Review of the Literature

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…While the probability of being arrested within 1 year was lower for the treatment group, and statistically significant, the gains were modest in practical terms. Doleac (2018) provides a comprehensive review of interventions designed to reduce recidivism and to promote employment, housing and health improvements among released felons. In general, a variety of approaches toward reemployment have been pursued.…”
Section: Existing Evidence On Reintegrating Ex-offenders Into Societymentioning
confidence: 99%
See 1 more Smart Citation
“…While the probability of being arrested within 1 year was lower for the treatment group, and statistically significant, the gains were modest in practical terms. Doleac (2018) provides a comprehensive review of interventions designed to reduce recidivism and to promote employment, housing and health improvements among released felons. In general, a variety of approaches toward reemployment have been pursued.…”
Section: Existing Evidence On Reintegrating Ex-offenders Into Societymentioning
confidence: 99%
“…Doleac (2018) provides a comprehensive review of interventions designed to reduce recidivism and to promote employment, housing and health improvements among released felons. In general, a variety of approaches toward re‐employment have been pursued.…”
Section: Existing Evidence On Reintegrating Ex‐offenders Into Societymentioning
confidence: 99%
“…Nevertheless, Bahr et al (2016), who use a randomized control trial to evaluate a cognitive behavioral program that combines cognitive training, goal setting, and a phone-coach follow-up, find no effects on arrests. Doleac (2018) reviewed the literature on re-entry programs in the U.S. and found that the programs that seem most promising are court-issued rehabilitation certificates, cognitive behavioral therapy, diversion from short incarceration spells, reducing intensity of community supervision, and expanding DNA databases. She found mixed evidence regarding the effectiveness of multisystemic therapy, and negative results on the effectiveness of transitional jobs programs, Ban the Box, and wrap-around services.…”
Section: Rehabilitationmentioning
confidence: 99%
“…People exiting jail and prison face a broad array of challenges that make it difficult to build a stable life and avoid criminal activity. On average, they have limited education and work experience, high rates of mental illness and emotional trauma, and high rates of substance abuse (Doleac, ; Doleac, ). In addition, many have accumulated substantial court debt and child support arrears, both of which tax legal income and may also result in the suspension of their driver's license (Ciolfi, Levy‐Lavelle, & Salas, ; Holzer, Raphael, & Stoll, ).…”
mentioning
confidence: 99%
“…In a recent review of empirical evidence on which programs reduce recidivism, I found some good news, some bad news, and many areas where the evidence is too thin to draw any conclusions (Doleac, ). Mental health interventions such as cognitive behavioral therapy (CBT) and family‐based multi‐systemic therapy have been shown to reduce recidivism (Heller et al., 2017; Sawyer & Borduin, ), though success is not guaranteed (Fonagy et al., ).…”
mentioning
confidence: 99%